Mindfulness and trauma recovery among internally displaced individuals: the mediating role of distress tolerance in a cross-sectional mediation model - Aldbyani, Aamer; Alhimaidi, Afnan; Chuanxia, Zhang (Frontiers in Psychology, 2025)
BackgroundMindfulness has gained increasing attention for its role in fostering emotional regulation and psychological resilience. In contexts of displacement and trauma, mindfulness may be associated with improved adaptive coping and recovery. This cross-sectional study investigated the relationships among mindfulness, distress tolerance, and trauma recovery in internally displaced individuals, with a focus on the mediating role of distress tolerance.MethodsA sample of 321 Yemeni internally displaced persons completed the Five Facet Mindfulness Questionnaire (FFMQ), the Distress Tolerance Scale (DTS), and the Posttraumatic Diagnostic Scale for DSM-5 (PDS-5).ResultsAnalysis revealed that all facets of mindfulness—observing, describing, acting with awareness, non-reactivity, and non-judgment—were positively associated with both distress tolerance and trauma recovery. Mediation models indicated that distress tolerance partially mediated the relationship between mindfulness and trauma recovery.ConclusionThese findings indicate the potential value of including mindfulness and distress-tolerance components in interventions for internally displaced populations.